Meningkatkan Kesadaran Masyarakat Tentang Aedes aegypti di Era Cuaca Ekstrem - Endris, Wahyu Maulana; Ali, Musyafa; Taufiq, Hameda Dhaka Kusuma; Wasito, Wasito (Society : Jurnal Pengabdian Masyarakat, 2024)
This community service the impact of community engagement activities on public knowledge regarding dengue fever and its prevention methods. Through pre- and post-tests conducted with 120 participants, a significant improvement in knowledge is observed after their participation in these activities. Previously, the majority of participants had limited knowledge, but after the intervention, approximately 80% of them demonstrated a better understanding. This success is not only reflected in the increased knowledge scores but also in the high level of participation, indicating the community's enthusiasm for supporting these awareness initiatives. The findings affirm the effectiveness of community engagement approaches in enhancing public knowledge and provide impetus for similar initiatives in the future. This achievement is pivotal in strengthening public awareness about health and disease prevention, laying a robust foundation for sustained community-level preventive efforts